JSLU, JSPACA, PKSA : Cash and In-Kind Transfers for At-Risk Youth, the Disabled, and Vulnerable Elderly - World Bank (World Bank, Jakarta, 2017)
Direct cash transfers for vulnerable elderly and disabled populations have been provided by the Ministry of Social Welfare (Kementerian Sosial, Kemensos) since 2006; a similar cash transfer for at-risk youth was inaugurated in 2009. The Government of Indonesia's (GoI) pro-poor development initiatives, international agreements and domestic laws and regulations, and considerable experience delivering more general social assistance programs led to the creation of cash transfers for these historically neglected and difficult-to-reach groups. These programs Jaminan Sosial Lanjut Usia (JSLU), Jaminan Sosial Paca Berat (JSPACA), and program Kesejahteraan Sosial Anak (PKSA) for the elderly, disabled, and youth respectively transfer cash directly to beneficiaries. They account for increasing shares of the Kemensos overall budget, but subsidies directed to care and rehabilitation facilities as well as direct provision of institutional care still account for a noticeable portion of the Kemensos budget for these groups. Program support operations socialization and outreach; allocation, targeting and prioritization; monitoring and evaluation; and complaints and grievances have very small budgets and depend crucially on cooperation and enthusiasm from local governments and facilitators. A full range of safeguarding activities is spelled out in program guidelines but these have not been institutionalized at the local implementation level. There is variation in the content, methods, frequency, completion rates, and outcomes in all safeguarding activities, and no easy-to-use reporting process that would ensure information from implementation level reaches the central funding and policy agency, Kemensos. The note summarizes quantitative and qualitative evidence in order to build a sound foundation for evaluating the cash transfer programs JSLU, JSPACA, and PKSA provided by Kemensos. The evidence on which the evaluation is based here is composed primarily of first-hand observation of the programs in operation. Where possible information collected from administrative records, including monitoring and evaluation reports, and from Kemensos itself, is summarized. Design features, efficiency and effectiveness of program implementation and operation, and impacts (intended or not) the program produces for beneficiaries are all analyzed in as much detail as possible. Current policy planning within Kemensos assumes expansion of these programs in the coming years, so an evaluation of the programs' features is relevant for Indonesian policymakers and stakeholders.